Spatiotemporal properties of cortical excitatory and inhibitory neuron activation by sustained and bursting electrical microstimulation - Christopher L. Hughes; Kevin C. Stieger; Keying Chen; Alberto L. Vazquez; Takashi D.Y. Kozai (iScience)
Summary: Intracortical microstimulation (ICMS) of sensory brain regions can create artificial sensations, yet these percepts fade with continued stimulation, suggesting dynamic changes in underlying neural activity. Using two-photon imaging in transgenic mice, this study examines how prolonged ICMS (30 s) shapes activity in excitatory and inhibitory neurons within the visual cortex. Inhibitory neuron activity was more likely to increase throughout the stimulation period, while excitatory neuron activity was more likely to decrease and be suppressed post-stimulation. Stimulation patterns differentially shaped neuronal engagement: theta-burst stimulation most effectively activated inhibitory neurons, whereas 10-Hz burst most effectively activated excitatory neurons. ICMS evoked more diverse responses in neurons farther from the electrode, reflecting complex synaptic interactions involving inhibition and disinhibition. These results show that ICMS affects excitatory and inhibitory neurons differently over extended durations. Modulation of stimulation patterns may allow for preferential engagement of specific neuron types and shaping of cortical activity.